Efeito do pré-tratamento do bagaço de cana na hidrólise ácida para obtenção de glicose - Carvalho, Janaína Alves (2015)
In this study it was evaluated the effects of pretreatments of biomass in the bagasse of sugar cane in the glucose yield after acid hydrolysis. This process is one of the steps in the production of second generation of ethanol that is achieved in low-income, being also, an obstacle to production in large-scale. Grinding was tested in a ball mill. The treatment with ultrasound was performed in various times, in acid solutions (HCl) and alkaline (NaOH) and in different concentrations. Hydrogen peroxide (3,5 and 7%) in an alkaline medium (pH= 11,) at different reaction times and temperatures were used. The Corona treatment was performed with variation in exposure time of the biomass to electrical discharge of the apparatus. The combined pretreatment consisted of grinding and ultrasound. After the biomass pretreatments, acid hydrolysis reactions and determination of total reducing sugars were performed (ART). X-ray analysis, optical microscopy and HPLC were performed. %ART and glucose larger values were obtained when the treatment with hydrogen peroxide and ultrasound in alkaline medium were used. The micrographs showed changes in the walls of the bagasse fibers in all treatments, wherein the material pre-treated with peroxide, the modifications, were more accentuated. There was an increase in the crystallinity of the materials treated compared to untreated bagasse in all treatments, indicating loss of amorphous material (hemicellulose and lignin), favoring the process. Thus, pre-treatment with alkaline hydrogen peroxide and ultrasound in alkaline medium were more efficient in relation to the glucose yield obtained after the acid hydrolysis reaction.